2017
DOI: 10.1016/j.dsr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Canyon effect and seasonal variability of deep-sea organisms in the NW Mediterranean: Synchronous, year-long captures of “swimmers” from near-bottom sediment traps in a submarine canyon and its adjacent open slope

Abstract: Numerous organisms, including both passive sinkers and active migrators, are captured in sediment traps together with sediments. By capturing these "swimmers", the traps become an extraordinarily tool to obtain relevant information on the biodiversity and dynamics of deep-sea organisms. Here we analyze near-bottom swimmers larger than 500 µm and their fluxes collected from eight near-bottom sediment traps installed on instrumented moorings deployed nearby Blanes Canyon (BC). Our data, obtained from November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A case in point is, for instance, the observations along the disturbed axis of the well-studied Nazaré Canyon that reported very low meiobenthos and nematode density and diversity levels (Garcia et al, 2007). In contrast, more diverse meiofauna (Bianchelli et al, 2013;Román et al, 2016), nematode (Danovaro et al, 1999;Bianchelli et al, 2013), macrofauna (Romano et al, 2013a;De Leo et al, 2014;Romano et al, 2017) and megafauna (Vetter et al, 2010;Ramirez-Llodra et al, 2010) communities in canyons than in the respective adjacent slopes have been observed. These studies (including our) are likely the result of having included a suitably diverse range of sites that well-represent the canyon landscape heterogeneity, together with the diversity of habitats one can find therein.…”
Section: Comparing Blanes Canyon With the Adjacent Western Slopementioning
confidence: 99%
See 1 more Smart Citation
“…A case in point is, for instance, the observations along the disturbed axis of the well-studied Nazaré Canyon that reported very low meiobenthos and nematode density and diversity levels (Garcia et al, 2007). In contrast, more diverse meiofauna (Bianchelli et al, 2013;Román et al, 2016), nematode (Danovaro et al, 1999;Bianchelli et al, 2013), macrofauna (Romano et al, 2013a;De Leo et al, 2014;Romano et al, 2017) and megafauna (Vetter et al, 2010;Ramirez-Llodra et al, 2010) communities in canyons than in the respective adjacent slopes have been observed. These studies (including our) are likely the result of having included a suitably diverse range of sites that well-represent the canyon landscape heterogeneity, together with the diversity of habitats one can find therein.…”
Section: Comparing Blanes Canyon With the Adjacent Western Slopementioning
confidence: 99%
“…Canyon benthic communities differ in terms of structure and functioning from the adjacent slope fauna located at equivalent depths (Vetter and Dayton, 1998;Duineveld et al, 2001; Garcia et al, 2007;Ingels et al, 2009;Gunton et al, 2015, Rosli et al, 2016Román et al, 2016). Furthermore, habitat heterogeneity and organic matter accumulation often support higher density and biomass in canyons, both locally and overall, compared to the adjacent open slopes (e.g., Grémare et al, 2002;Curdia et al, 2004;Ingels et al, 2009;De Leo et al, 2010;Huvenne et al, 2011;Romano et al 2013a;Leduc et al, 2014;Romano et al 2017). This phenomenon is generally referred to as "canyon effects".…”
Section: Introductionmentioning
confidence: 99%
“…Submarine canyons are environmentally important areas for the megafauna dynamism and the ecology of multiple species. These structures have an effect on the deep-sea species assemblages both within the area itself and on the neighboring open slope (Romano et al, 2017;Tecchio et al, 2013), which populations may be interconnected due to eggs and larval dispersal by water current dynamics, as for the case of Aristeus antennatus (Clavel-Henry et al, 2020). Some benthic communities undertake seasonal and ontogenetic migrations between the canyon area and the open slope, which are detected by observation of the specimen sizes and the distribution of fishing effort throughout the year, as for the case of A. antennatus (Sardà et al, 1997;Sardà et al, 2003a;Tudela et al, 2003) and Merluccius merluccius (Stefanescu et al, 1994).…”
mentioning
confidence: 99%